Citizenship and Citizenship Education: What happens in the classroom of a public university in Madrid where future elementary school teachers are being trained? - Héctor Cárcamo-Vásquez (Universidad Nacional, Costa Rica, 2015)
The objective of this article is to understand the way in which the startup training for teachers affects the social representation setup of students, who study to become teachers, over the citizenship and the citizenship education developed by the school. The methodology used is qualitative with an ethnographic approach, and the main technique used is the observation of the participants. The results show that the way in which prospective teachers understand citizenship education in school is mediated by the vision of education centered in pedagogical technical aspects. Thus, they emphasize the role of the didactic as a tool to ensure their students learning how to teach, the group of guidelines and values which allow them to reproduce the social order at school as well as in the society where they are a part of.